2005
DOI: 10.1209/epl/i2004-10382-3
|View full text |Cite
|
Sign up to set email alerts
|

Shape fluctuations and elastic properties of two-component bilayer membranes

Abstract: Abstract. -The elastic properties of two-component bilayer membranes are studied using a coarse grain model for amphiphilic molecules. The two species of amphiphiles considered here differ only in their length. Molecular Dynamics simulations are performed in order to analyze the shape fluctuations of the two-component bilayer membranes and to determine their bending rigidity. Both the bending rigidity and its inverse are found to be nonmonotonic functions of the mole fraction xB of the shorter B-amphiphiles an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 36 publications
10
57
1
Order By: Relevance
“…Both tensions have been recently measured in molecular dynamics simulations and were found to be different in magnitude (Imparato et al 2005).…”
Section: Bending Rigidity Stretching Elasticity and Spontaneous Curvmentioning
confidence: 92%
“…Both tensions have been recently measured in molecular dynamics simulations and were found to be different in magnitude (Imparato et al 2005).…”
Section: Bending Rigidity Stretching Elasticity and Spontaneous Curvmentioning
confidence: 92%
“…The temperature of the system is maintained at k B T/ε = 0.22 by employing the Nose-Hoover thermostat. The model was implemented in the NAT ensemble [56,77,78]. Given that the diameter of the lipid particles is The timestep of the simulation is selected to be Δt = 0.01t s .…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Hence, a more accurate determination of the true bilayer area is necessary to calculate area compressibility in large bilayer patches. Using a similar model for amphiphilic molecules (single-chain), Imparato et al [77] have shown that the bending rigidity of a two-component bilayer, in which the two amphiphiles differ only in tail length, exhibits a nonmonotonous behavior as function of bilayer composition. A similar functional dependence was found by Brannigan and Brown [56] using an implicit solvent, particle-based model.…”
Section: Empirical Coarse-grained Modelsmentioning
confidence: 99%
“…It is however important to note that, if the bilayer undergoes large fluctuations and undulations, the value of the area per lipid computed in this way is underestimated (see e.g. [77]). …”
Section: A2 Structural Properties Of Lipid Bilayersmentioning
confidence: 99%